2014
DOI: 10.1111/bju.12902
|View full text |Cite
|
Sign up to set email alerts
|

The conservative management of renal trauma: a literature review and practical clinical guideline from Australia and New Zealand

Abstract: Objective• To review the literature and make practical recommendations regarding the conservative management of renal trauma. Patients and Methods• Relevant articles and guidelines published between 1980 and 2014 were reviewed.• Graded recommendations were constructed by a multi-disciplinary panel consisting of urologists, radiologists, and infectious disease physicians. • These recommendations underwent formal review and debate at the Western Australian USANZ 2013 state conference, and were presented at the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
20

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 55 publications
1
53
0
20
Order By: Relevance
“…1,4 Of a total of 27 patients, 77.8% had other solid organ injuries, and there was no difference between rates of splenic and liver injuries. Santucci et al, in a systematic review of renal trauma, demonstrated a significant variation in complication rate between the series revised, ranging from 0 to 34%, with a mean of 10%.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…1,4 Of a total of 27 patients, 77.8% had other solid organ injuries, and there was no difference between rates of splenic and liver injuries. Santucci et al, in a systematic review of renal trauma, demonstrated a significant variation in complication rate between the series revised, ranging from 0 to 34%, with a mean of 10%.…”
Section: Discussionmentioning
confidence: 96%
“…These findings indeed reinforce the results of the Eastern Association for the Surgery of Trauma's practice guidelines for this topic from 2004. 4 …”
Section: Nonoperative Management Of Blunt Renal Traumamentioning
confidence: 99%
See 2 more Smart Citations
“…Literatūroje aprašoma, jog didesnis inksto sužalojimo laipsnis lemia gausesnį kraujavimą į retroperitoninį tarpą ir dažniau nulemia pacientų hemodinamikos nestabilumą [14,20,21]. Tai atsispindi ir mūsų tyrimo duomenyse: gautas stiprus teigiamas ryšys tarp KT nustatyto inksto plyšimo laipsnio ir KT vaizduose išmatuoto retroperitoninio tarpo hematomos tūrio.…”
Section: Rezultatų Aptarimasunclassified